Pelvic reconstruction after partial acetabular resection of bone sarcoma - Wong, Kwok-Chuen; Niu, Xiaohui; Xu, Hairong; Li, Yuan; Kumta, Shekhar Madhukar (Annals of Joint; Vol 4 (April 2019): Annals of Joint, 2019)
Tumour surgeons have to achieve a negative resection margin for the best oncological outcomes with the reduced risk of local recurrence and improved patient survival. Given that the pelvic bone has a complex geometry with intricately related vital neurovascular structures, surgeons may resect tumours with more margin than oncologically necessary when taking into account the inaccuracy in planning and resection. The lesser normal bone may be retained for reconstruction to restore limbs function. Therefore, bone sarcoma locating near the acetabulum is often resected including the entire acetabulum. Partial acetabular resection of bone sarcoma with pelvic reconstruction has been described in selected patients with periacetabular tumours in a few case series. Early promising results were reported with the advantages of preserving more host bone for reconstruction without compromising the oncological resection margin and increasing the risk of local recurrence when the surgeries were performed with good preoperative planning and guided resection under computer navigation guidance. This article is to review the pelvic reconstruction after partial acetabular resection of bone sarcoma, its pathoanatomy, surgical considerations, current evidence and limitations.